DTI and Myelin Plasticity in Bipolar Disorder: Integrating Neuroimaging and Neuropathological Findings - Bellani, Marcella; Boschello, Filippo; Delvecchio, Giuseppe; Dusi, Nicola; Altamura, Carlo Alfredo; Ruggeri, Mirella; Brambilla, Paolo (Frontiers in Psychiatry, 2016)
Bipolar disorder (BD) is a major psychiatric illness with a chronic recurrent course, ranked among the worldwide leading disabling diseases. Its pathophysiology is still not completely understood, and findings are still inconclusive, though a great interest on the topic has been constantly raised by magnetic resonance imaging (MRI), genetic and neuropathological studies. In recent years, diffusion tensor imaging (DTI) investigations have prompted interest in the key role of White Matter (WM) abnormalities in BD. In this report we summarized and commented recent findings from DTI studies in BD, reporting fractional anisotropy (FA) as putative measure of WM integrity, as well as recent data from neuropathological studies focusing on oligodendrocyte involvement in WM alterations in BD. DTI research indicates that BD is most commonly associated with a WM disruption within the fronto-limbic network, which may be accompanied by other WM changes spread throughout temporal and parietal regions. Neuropathological studies, mainly focused on the fronto-limbic network, have repeatedly shown a loss of oligodendrocyte cell count underlying WM alterations, although an increased oligodendrocyte density has been also documented suggesting a putative role in remyelination processes for oligodendrocytes in BD. According to our review, a greater integration between DTI and morphological findings is needed in order to elucidate processes affecting WM, either glial loss or myelin plasticity, on the basis of a more targeted research in BD.